Elucidation of the influence of operating temperature in LiNi0.8Co0.15Al0.05O2/silicon and LiNi0.8Co0.15Al0.05O2/graphite pouch cells batteries cycle-life degradation. (September 2021) - Farmakis, F.; de Meatza, I.; Subburaj, T.; Tsiplakides, D.; Argyropoulos, D.-P.; Balomenou, S.; Landa-Medrano, I.; Eguia-Barrio, A.; Strataki, N.; Nestoridi, M.
Highlights: Direct comparison between LiNi0.8Co0.15Al0.05O2/silicon and LiNi0.8Co0.15Al0.05O2/graphite pouch cells at 5, 25 and 35 o C operation. Silicon-anode pouch cells with more than 120 cycles before losing 20% of their initial capacity at 5 and 25 o C. Capacity fading mechanism of the LiNi0.8Co0.15Al0.05O2/silicon varies according to the operation temperature. Abstract: The necessity for lighter and smaller energy storage systems drives the technological limits to electrochemical systems that offer higher gravimetric and volumetric energy density. Toward this trend, silicon as anode material provides a great potential due to the high specific capacity but lacks stability over extensive cycling. In this paper, we present a comparative study between LiNi0.8 Co0.15 Al0.05 O2 /silicon and LiNi0.8 Co0.15 Al0.05 O2 /graphite pouch cells with the aid of electrochemical impedance spectroscopy (EIS). The two pouch cell systems were manufactured and underwent galvanostatic cycling at 5, 25 and 35 °C, monitoring cell capacity and impedance. The results demonstrated, as expected, that capacity fade in silicon-anode pouch cells is faster than with graphite-anode at all temperatures. However, silicon-anode pouch cells are able to perform more than 120 cycles at C/10 charge and C/2 discharge rates before losing 20% of their initial capacity at 5 and 25 °C. At these temperatures, the decay of the capacity is mostly attributed to the degradation of the silicon anode. By combining EIS spectra, differential voltage and post-mortem analysis, it is suggested that when the silicon-based cells are cycled, anode degradation contributes to NCA cathode damage due to the overvoltage. Therefore, we suggest that besides the silicon degradation, the NCA cathode plays also a role in the cycling lifetime of the silicon-based cells.